Explanation:
so, we are going to use the slope-intercept form
f(x) = y = ax + b
"a" being the slope, "b" being the y-intercept (the y-value when x = 0).
the slope is as always the ratio (y coordinate difference / x coordinate difference) when going from one point on the line to another.
so, when using these 2 given points
x changes by -3 (from -6 to -9).
y changes by +1 (from -2 to -1)
the slope "a" is
+1/-3 = -1/3
"b" we get by using the coordinates of one of the points, e.g. (-6, -2) :
-2 = -1/3 × -6 + b = 2 + b
-4 = b
so the functional equation is
f(x) = (-1/3)x - 4